Construction of Novel Bispecific Single-Domain Antibodies (BiSdAbs) with Potent Antiangiogenic Activities - Liu, Xianglei; Sun, Tianyuan; Ge, Qiuhan; Zhu, Jianwei (Pharmaceutical Fronts, 2020)
The development of bispecific antibodies (BsAbs) has had a profound impact on cancer immunotherapy. Single-domain antibodies (SdAbs) could offer advantages over other antibody formats for the generation of a BsAbs, such as small size (∼12–15 kDa), with high affinity and specificity, superior accessibility, and high yield expression in bacteria. In this study, VEGFR2 and CD16 were chosen as the targets to construct BsAbs. As the rationale, VEGFR2 is critical for tumor-associated angiogenesis, and CD16 expressed on natural killer cells is an important target on immune cells. Humanized anti-VEGFR2 SdAb 3VGR19 and anti-CD16 SdAb C21 were combined to construct several bispecific SdAbs (BiSdAbs). The biochemical properties of the BiSdAbs were characterized. They retained the high affinity for both targets, binding selectivity, and antiangiogenic activity such as inhibition of cell proliferation, migration, endothelial tube formation, angiogenesis, and cytotoxicity to cancer cells in vitro, indicating that BiSdAbs could be a potential alternative for cancer therapy.
Keywords: bispecific antibody; single-domain antibodies; nanobody; BiSdAb